Expanded Perlite Mineral As a Natural Additive Used In Polylactide-Based Biodegradable Composites - Aksoy, Erkan; Tirkeş, Süha; Tayfun, Ümit; Tirkeş, Seha (Fırat Üniversitesi, 2024)
Polylactide (PLA) is a biodegradable polymer derived from natural resources used in various applications ranging from medical to packaging. In this study, biocomposites were developed by combining perlite mineral (PER), a natural filler material, with a biodegradable PLA matrix in incorporated contaminations of 2.5%, 5%, 10%, and 15%. The purpose of this work is to obtain composites having low production costs while retaining their main properties. Mixing force measurements, tensile, Shore hardness, impact tests, melt flow indices (MFI), and scanning electron microscopy (SEM) evaluations were carried out on composite samples to determine the processing, mechanical, melt flow, and morphological aspects of the developed composites. When the tensile test data were reviewed, minor decreases in the tensile strength and % elongation parameters were noticed with perlite loadings. The inclusion of perlite powder significantly reduced the impact strength value of PLA. Composites with high amounts of PER displayed elevated hardness values. While the MFI results were analyzed, it was deduced that the addition of PER increased the melt flow characteristics of the PLA polymer. At low PER quantities, SEM micrographs displayed that PER particles were homogeneously distributed in the PLA phase. The particle homogeneity in the composite morphology deteriorated as the PER loading ratio in the composites rose. According to the overall results, the highest performance among composites was achieved in the sample including 2.5% PER, and this sample was considered to be the most suitable option for applications regarding PLA-based biocomposite material purposes.

Polilaktit (PLA), tıptan paketlemeye kadar çeşitli uygulamalarda kullanılan, doğal kaynaklardan elde edilen ve biyolojik olarak parçalanabilen bir polimerdir. Bu çalışmada, biyokompozitler, doğal bir dolgu malzemesi olan perlit mineralinin (PER) biyolojik olarak parçalanabilen bir PLA matrisi ile %2.5, %5, %10 ve %15'lik ekleme oranlarında harmanlanarak hazırlanmıştır. Geliştirilen kompozitlerin işlenme, mekanik, erime akışı ve morfolojik özelliklerini belirlemek için kompozit numuneler üzerinde karıştırma kuvveti ölçümleri, çekme, Shore sertliği, darbe testleri, erime akış indisleri (MFI) ve taramalı elektron mikroskobu (SEM) değerlendirmeleri yapılmıştır. Çekme testi verileri incelendiğinde, perlit yüklemeleri ile çekme mukavemeti ve % uzama parametrelerinde ufak düşüşler görülmüştür. Perlit tozunun dahil edilmesi, PLA'nın darbe dayanımı değerini önemli ölçüde azaltmıştır. Yüksek miktarda PER içeren kompozitler, yüksek sertlik değerleri göstermiştir. MFI sonuçları analiz edildiğinde, PER ilavesinin PLA polimerinin erime akış özelliklerini arttırdığı bulunmuştur. Düşük PER miktarlarında, SEM mikrografları, PER partiküllerinin PLA fazında homojen bir şekilde dağıldığını ortaya çıkarmıştır. Kompozit morfolojisindeki partikül homojenliği, kompozitlerdeki PER yükleme oranı arttıkça bozulmuştur. Genel sonuçlara göre kompozitler arasında en yüksek performans %2,5 PER içeren numunede elde edilmiş ve bu numunenin PLA esaslı biyokompozit malzeme amaçlı uygulamalar için en uygun seçenek olduğu değerlendirilmiştir.
Polilaktid Esaslı Biyobozunur Kompozitlerde Doğal Bir Katkı Maddesi Olarak Genişletilmiş Perlit Mineralinin Kullanımı
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri; Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler; Polymers and Plastics; Polimerler ve Plastikler